Undergraduate research monitoring model in construction engineering and management. - Osama Abudayyeh (Journal of construction engineering and management)
The construction industry is a major player in the nation's economy. The complex nature of the construction industry, coupled with the challenges of global competitiveness and changing regulatory requirements, has created the need for providing higher levels of education, experience, and training for construction professionals. An essential and integral component of the required education and training must be the research training undergraduate civil and construction students, encouraging them to pursue advanced education and research careers in this area. With this in mind, the writer developed a Research Experiences for Undergraduates (REU) summer program at Western Michigan University that focuses on construction engineering and management issues and problems. This construction-oriented undergraduate research training program is the REU site in the United States to be funded by the National Science Foundation. This paper will describe the structure of the REU program, the types of activities undertaken by the REU participants, and the results of the program evaluation and assessment.